Influence of glutamine on the effect of resistance exercise on cardiac ANP in rats - Romeu Rodrigues de Souza; Cleomara Angélica Vieira Caldeira; Patrícia Oliva Carbone; Eduardo Victor Pianca (Revista Brasileira de Ciências do Esporte, 2015)
Various nutritional supplements (herbs, vitamins, and micronutrients) improve responses and adaptations to resistance exercise. ANP is a heart hormone that contributes to fluid, electrolyte and blood pressure homeostasis through its natriuretic and vasodilative actions. In the present study, the adaptation of ANP in response to resistance exercise was investigated in rats supplemented with glutamine for five weeks. The results showed that supplementation with glutamine did not influence the number of ANP granules per atrial cardiocyte in sedentary animals. In exercised-trained rats, the number and diameter of the granules was significantly higher in comparison with the control group and in exercised animals supplemented with glutamine there was significant increase in the number and diameter of ANP granules compared with controls. Altogether, these data indicated that in resistance exercise rats, glutamine significantly enhances cardiac ANP thus implicating the beneficial effects of glutamine supplementation to the ANP system.